GROSS NITROGEN AND PHOSPHORUS BALANCE IN THE POLISH AGRICULTURE AGAINST THE BACKGROUND OF SELECTED EUROPEAN UNION MEMBER STATES AND THE HELCOM GROUP - Jerzy Kopiński; Beata Jurga; Wioletta Wrzaszcz (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2024)
The aim of the study is the comparative analysis of the of gross nitrogen (N) and phosphorus (P) balances in Poland and selected EU countries and those belonging to the HELCOM group. The scope of the analysis covered the years 2011-2019. The main source of information was Central Statistical Office of Poland and EUROSTAT statistical data. A comparative analysis of the gross nitrogen and phosphorus balances for the surveyed EU Member States and regions (HELCOM) indicates the diversity of results, trends of changes and approaches in their management over the years. The study showed that the gross nitrogen balance was positive in all analysed years, in the HELCOM Group countries. The average gross nitrogen balance surplus for Poland in 2011-2019 was slightly below 50 kg N/ha UAA and this was below the average level observed for all EU-27 Member States, but higher than the average for the HELCOM Group. In most of the analysed countries, there was a positive phosphorus balance over 9 years. Phosphorus deficits (on average for the entire period) were recorded only in Germany and Romania. Poland does not stand out significantly in terms of the average balance of gross phosphorus in agriculture, which on average in 2011-2019 amounted to an average of 2.7 kg P/ha UAA. Both in Poland and for the compared groups of countries, the highest balance of phosphorus balance was recorded in the first period of the analysis, i.e. in 2011-2013, this reducing trend should be considered a positive phenomenon as it is a sign of reduced agricultural pressure on the environment.